The Students’ Difficulties in Identifying the Five Verb Forms on the News Item Text at NHU Pematangsiantar - Melda Veby Ristella Munthe (International Journal of Educational Research Excellence (IJERE), 2024)
The way people communicate is communication. Communication needed meaning. The meaning which contained of the sentence has the differences of meaning form. The problem of this research is the difficulties of the students’ in identifying the five verb forms in English. The aimed of this research is identifying the findings of the students’ errors in stating which formed contained of it. It can be Base (Regular): (To) laugh, Past tense: Laughed, Past Participle: Laughed, Present Participle: Laughing and Third-Person Singular: Laughs. The method applied qualitative research. The subject is the students in the third semester. The instrument of the data is a written test. The researcher made steps how to analyse the data namely: Counted the vocabulary which contained of the verb forms, Classified it by making them a code into their groups, Founded the variant of the difficulties in identifying verb forms that written by the students mostly, and described it. The student’s difficulties in identifying the five verb forms on the text entitled “Hundreds of thousands affected by floods, landslides as heaviest rain in 60 years hits southern China” got the highest one is very good category with 48 students with 81,3%, then followed by the good category with 5 students on the 8,4%, 2 students with low category namely 3,3%, and the last fair category with 4 students on the 6,7%. It found the dominantly applied by the students in identifying the difficulties is stated to the Nouns became Verbs, The Preposition became Verbs, and the most of the students’ difficulties in differentiate the correct verb forms, if it’s a V2 (Preterit) or V3 (Past Participle) form